أسلمة المعرفة في الشعر العربي بين الجاهلية والإسلام: شعر حسان بن ثابت في المدح أمنوذجا: Islamization of Arabic Poetry between Pre-Islamic (Jahiliyyah) and Islamic Period: Praise Poetry of Hassan Ibn Tsabit as a Case Study - Nor Hidayah binti Suleiman,; Rahmah Binti Ahmad H. Osman,; Asma’ Huda binti Rosli,; Anis Farzana binti Azhar, (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2021)
ملخص كان حسان بن ثابت له مكانة كبيرة في الشعر العربي والمواهب والمواهب الشعرية لديه ملكة ورثه من عائلته كأحد العائلة الشعراء المرموقين. وهو رضي الله عنه شاعر مشهور في الجاهلية بين قومه وكذلك الحال في عصر الإسلام بعد اسلامه وحسن اسلامه. والجدير بالذكر، أنه قد لعب دورا كبيرا في الدفاع عن رسالة الإسلام خلال أشعاره وقصائده. تهدف هذا البحث إلى اكتشاف تغيرات التي تطرق في شعر حسان بن ثابت بين العصر الجاهلية وبعد الإسلام. اعتمدت المقالة على المنهج الوصفي المكتبي وركز البحث في شعر المدح. وقام الباحثون بتحليل شعر مدح لحسان بن ثابت اعتمادا على منهج إسلامية المعرفة الأدب الإسلامي لمحمد عثمان المحمدي. وتوصلت البحث إلى أن شعر حسان بن ثابت تأثر بالإسلام من حيث المصطلحات والأساليب تأثرا عميقا. Abstract Hassan bin Tsabit is among the prominent figures in Arabic poetry. One of the reasons he excels in poetry is because he is from a family of poets. Hassan bin Tsabit is well-known among his people during the pre-Islamic (jahiliyah) period and during the Islamic period after his conversion to Islam. It is a known fact that he plays a big role in defending Islam through his poetries. On that note, this article aims to find out the islamization in Hassan bin Tsabit's poetry works between pre-Islamic and Islamic period focusing on his praise poetries. The methodology used for this article is the descriptive qualitative research method. The researchers analyzed the selected praise poetries according to the concept of Islamic literature by Muhammad Uthman El-Muhammady. The findings of this article are that the work of praise poetries by Hassan bin Tsabit is influenced strongly by Islam in terms of the terminologies and style of writing.